Progress and hotspot of diet or exercise therapy in the treatment of non-alcoholic fatty liver disease - Shi, Xinyu; Xiong, Yalan; Song, Hualing; Rong, Fen; Tang, Nan; Zhu, Leping; Li, Shenyu; Wang, Jianying; Zhang, Lei; You, Shengfu; Ji, Guang; Liu, Baocheng; et al. (Frontiers in Nutrition, 2024)
The primary treatment for non-alcoholic fatty liver disease (NAFLD) is modifying lifestyle through dietary or exercise interventions. In recent decades, it has received increasing attention. However, the lack of bibliometric analysis has posed a challenge for researchers seeking to understand the overall trends in this field. As of February 3rd, 2024, 876 articles on treating NAFLD through diet or exercise therapy from 2013 to 2023 had been retrieved. Two software tools, VOSviewer and CiteSpace, were utilized to analyze the growth of publications, countries, institutions, authors, journals, citations, and keywords. Additionally, the keywords with strong citation burstiness were identified to determine the changes and future trends of research hotspots in this field. China had the highest number of articles, followed by the United States and South Korea. Yonsei University and Nutrients were the institutions and journals with the most significant contributions. Professor Younossi Zobair M, from the United States, is the most prolific author in this field. Through analyzing the keywords, three research hotspots were identified: research on the pathogenesis of NAFLD, research on the treatment modalities of NAFLD, and research on the risk factors and diagnosis methods of NAFLD. In recent years, the research emphasis in this field has changed, suggesting that future research will focus on two frontier keywords: “oxidative stress” and “aerobic capacity”.